Pengembangan Kemasan UMKM Tahu Di Kelurahan Lewirato Kota Bima - Ita Purnama; Hanifa Nuri Santi; Rena Trifebrianti; Sarina Sarina (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
Tofu is a food that many people are interested in. Therefore, the tight competition in the business world makes entrepreneurs strive to improve the quality in developing tofu packaging on the market. So the marketing strategy through packaging development for tofu needs to be improved so that it is popular with consumers. Developing awareness. This is a channel to attract potential buyers. Therefore, packaging in tofu is a product strategy, by improving the external shape of the tofu product, such as wrapping, labeling, color and so on. In order to fulfill the achievements in selling tofu products, it is necessary to understand the development of packaging for tofu. So that the tofu that we make for consumers can be attracted by the quality that we offer in the form of tofu packaging. One thing that needs to be provided with this information is UMKM players who are the biggest contributors to the national economy. The target for developing tofu packaging is UMKM players in the Lewirato sub-district. The development of tofu packaging is to increase the ability of UMKM players to market tofu products through packaging development so that they can increase UMKM players sales volumes.